2021
DOI: 10.13168/agg.2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Real-time cycle slip detection and repair for BDS-3 triple-frequency and quad-frequency B1C/B1I/B3I/B2a signals

Abstract: This paper presents a real-time cycle slip detection and repair strategy for the BDS-3 triplefrequency and quad-frequency phase observations. For the triple-frequency phase observations, two EWL code-phase combinations and one GF-phase combination are jointly employed to detect and repair cycle slips. Based on the different performances in the success of cycle slip detection and repair, this paper uses GF-phase combinations to detect and repair cycle slip individually. Specifically, the GF-phase combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For most civil receivers, B2b signals of BDS-3 cannot be received [53]. And combined with relevant literature, some common frequency combinations are listed in Table 3 [9,14,35,36,41,42,[53][54][55]. For convenience, all frequency combinations in Table 3 satisfy the relationship of…”
Section: Linear Combination Of Carrier-phase Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For most civil receivers, B2b signals of BDS-3 cannot be received [53]. And combined with relevant literature, some common frequency combinations are listed in Table 3 [9,14,35,36,41,42,[53][54][55]. For convenience, all frequency combinations in Table 3 satisfy the relationship of…”
Section: Linear Combination Of Carrier-phase Observationsmentioning
confidence: 99%
“…It should be noted that in Equation (36), the first two rows of matrix B are obtained according to the arrangement order of Equation (34). In other cases, if the arrangement order changes, B needs to be modified accordingly.…”
Section: Pseudorange Multipath Delay Combinationmentioning
confidence: 99%
“…Reasonably eliminating or reducing the effects of these errors can effectively improve the positioning accuracy [11][12][13][14]. Previous studies have shown that a reasonable combination of multiple frequency observations can reduce the impact of these errors, such as ionosphere-free combinations, ionosphere-reduced combinations, and geometric-free combinations [15][16][17][18][19][20]. With the increasing number of transmission signals, there are more favorable combinations available.…”
Section: Introductionmentioning
confidence: 99%